EVALUASI SIFAT FISIKO-KIMIA MINYAKGORENGYANG DIGUNAKAN OLEH PEDAGANG MAKANAN JAJANAN DI KECAMATAN TAMPAN KOTA PEKANBARU - Dewi Fortijna Ayu; Fareda Hamjm Hamzah (Jurnal Sagu, 2010)
The research objective was to evaluate physicochemicai characteristic of frying oil which has ueenused by food sellers on the street located In Timpan Subdistrict, Oty of Pekanbaru. The result showed thatfood setters didn't buy frying oil blended with used oil from restaurant, but unpackaged frying ofl in the smallshop. The}' nrixed unpackaged frying oil with their used frying oil in order to increase the oil volume. Foodsellers used the oil for continuous frying until 2-3 times for animal products and 10-13 times for vegetableproducts. The physicochemicai characteristic of unpackaged frying oil were; water content of 0346%, wastecontent of1.008%, free fatty acid content of OMS'/t, peroiide number of 29.958 Meq/kg, density valne of0.904, andfaidinenunriter of 51.515. After continuous frying, the physicochemicai characteristics of fryingoil was decreased. Used frying oil for animal products has waste contentof 5.187%, free fatty acid content of42 *<, peroxide number of35.407 Meq/kg, density value of 0.910, and iodine number of40.776 after two.8/ itimes frying. Used frying oil for vegetable products has waste content of6.084%, free fatty acid content of4.28%, peroxide number of53.908 Meq/kg, density value of 0.914, and iodine number of32.429 after tentimes frying. The reduction of physicochemicai characteristic of used frying oil for vegetable products ishigher than animal products